Nuclear-follower feeding associations between Geophagus brasiliensis (Teleostei: Cichlidae) and Deuterodon iguape (Teleostei: Characidae) in a coastal stream of southeastern Brazil - Souza, Gabriel R. S. [UNESP]; Sabine, Jose; Burmester, Cristiano F.; Garrone-Neto, Domingos [UNESP] (Verlag Dr Friedrich Pfeil, 2020)
Nuclear-follower feeding associations between Geophagus brasiliensis and Deuterodon iguape were described through underwater observations made at a costal stream of the Atlantic Forest, southeastern Brazil. Subadults of D. iguape were recorded feeding on sediment clouds suspended and expelled during the feeding activity of solitary adults of G. brasiliensis, mainly under organic substrate, during the day. The feeding association between G. brasiliensis and D. iguape represents the third record of this type of interaction along coastal drainages of South America, which increases to thirteen the number of known nuclear species in freshwater environments on the continent. The following behaviour is known to provide feeding benefits to follower and nuclear fishes in marine environments, and the present record reinforces that species into freshwater habitats are likely to have similar advantages when taking part in these interactions.